Juventudes : o projeto social como um dos espaços para a construção da socialidade juvenil - Silva, Silvia Gama da (2015)
This study is a reflection on the socio-cultural spaces that contribute to the construction of youth socialities. Fot this research, which was lined on a qualitative approach, it was opted by the ethnographic case study . The research field was a Social Project that meets young people in a city of Rio Grande do Sul, wherewith it was possible through the testimony of young people, and also educators, investigate this space and its contribution to the construction of youth socialities. Data collection was extended from April to December 2014 by participant observation, document analysis and semi-structured interview and the conversation wheel. Data were analyzed through Discoursive Textual Analysis, as taught Moraes and Galiazzi (2011) and resulted in the following categories: The social project in the vision of young people: Being young is be not old, In the presence of the other we constitute me and is necessary learn to live in the project; The social project in the view of educators who work there: Subject class that resist all the time - unruly and youth in social vulnerability. The survey findings confirm the importance of Social Project in the constitution of identities and subjectivities of young people who participate. The study found that even many of the practices put into operation at the Project refer to an idea that the youth needs to be "made docile", learn to meet promptly and follow rules. However, it also found that young people find loopholes for strength and leadership.